Environmental effects of anticholinesterasic therapeutic drugs on a crustacean species, Daphnia magna - Rocha, R.
The presence of pharmaceutical drugs in the environment is an important field of toxicology, since such residues can cause deleterious effects on exposed biota. This study assessed the ecotoxicological acute and chronic effects of two anticholinesterasic drugs, neostigmine and pyridostigmine in Daphnia magna. Our study calculated 48 h-EC50 values for the immobilization assay of 167.7 μg L(-1) for neostigmine and 91.3 μg L(-1) for pyridostigmine. In terms of feeding behavior, we calculated a 5 h-EC50 for filtration rates of 7.1 and 0.2 μg L(-1) for neostigmine and pyridostigmine, respectively; for the ingestion rates, the calculated EC50 values were, respectively, 7.5 and 0.2 μg L(-1) for neostigmine and pyridostigmine. In the reproduction assay, the most affected parameter was the somatic growth rate (LOECs of 21.0 and 2.9 μg L(-1) for neostigmine and pyridostigmine, respectively), followed by the fecundity (LOECs of 41.9 and 11.4 μg L(-1) for neostigmine and pyridostigmine, respectively). We also determined a 48 h-IC50 for cholinesterase activity of 1.7 and 4.5 μg L(-1) for neostigmine and pyridostigmine, respectively. These results demonstrated that both compounds are potentially toxic for D. magna at concentrations in the order of the μg L(-1).